Can the Use of ?-Adrenergic Blockers for Treatment of HFpEF Worsen Diastolic Dysfunction? - A Review Based on Concept of MyBP-C - Dookhun, Muhammad Nabeel; Doseiah, Pooja; Cao, Yunshan; Zhang, Ji-Nan; Lu, Xin-Zheng (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2017)
Heart failure can be classified based on ejection fraction as reduced Heart Failure Reduced Ejection Fraction (HFrEF), moderate Heart Failure Moderate Ejection Fraction (HFmEF) and preserved Heart Failure Preserved Ejection Fraction (HFpEF). Indeed, use of beta-blockers in Heart Failure (HF) reduces mortality and morbidity. However, the controversial effect of the use of beta-blockers in HFpEF is of great concern. HFpEF is associated with a high mortality and hospitalization rate probably due to lack of evidence-based treatment. Hence a proper understanding behind the pathophysiologic mechanism of HFpEF is important. Recently Myosin Binding Protein C